Optimal Timing of Systemic Therapy in Resectable Colorectal Liver Metastases. Issue 4 (April 2013) - Ihemelandu, Chukwuemeka; Levine, Edward A.; Aklilu, Mebea; Yacoub, George; Howerton, Russell; Bolemon, Britt; Graham, Matthew; Russell, Greg; Shen, Perry
Perioperative chemotherapy has been shown to improve disease-free survival compared with surgery alone for resectable colorectal liver metastases (CLM). We examined our experience with systemic chemotherapy in this clinical setting. A prospectively collected liver surgery database identified 210 patients treated for resectable CLM from 1996 to 2010. Results were correlated to four treatment groups: posthepatectomy adjuvant only, prehepatectomy preoperative only, peri-operative (preoperative and adjuvant), and surgery only. Seventy-nine (37.6%) patients received posthepatectomy adjuvant only treatment, 33 (15.7%) received prehepatectomy preoperative only treatment, 46 (21.9%) received perioperative (preoperative and adjuvant) treatment, whereas 52 (24.8%) received surgery alone. Preoperative and adjuvant systemic chemotherapy regimens were as follows: 23 (29.1%) and 18 (14.4%) received a 5-fluorouracil monotherapy regimen, 19 (24.1%) and 31 (24.8%) received an irinotecan-based regimen, and 28 (35.4%) and 37 (29.6%) received an oxaliplatin-based regimen. Nine (11.4%) and 12 (9.6%) received some other unknown combination. Treatment groups showed no difference in gender, mean tumor size, number of tumors, margin status, or postoperative complications with the only difference being a higher incidence of metachronous tumors in the preoperative only and perioperative groups (P = 0.01). Median follow-up and overall survival were 25 and 41 months, respectively. The adjuvant, preoperative, perioperative, and surgery only groups had a median survival time of 48, 35, 39, and 29 months, respectively (log-rank P = 0.04). Independent predictors of overall survival on multivariate analysis included treatment algorithm used and postoperative complication status. Adjuvant only systemic therapy was associated with an improved survival in resectable CLM. Prospective randomized trials are needed to confirm these findings.